Particulate matter pollution in Chinese cities: Areal-temporal variations and their relationships with meteorological conditions (2015–2017). (March 2019) - Li, Xiaoyang; Song, Hongquan; Zhai, Shiyan; Lu, Siqi; Kong, Yunfeng; Xia, Haoming; Zhao, Haipeng
Abstract: As the second largest economy in the world, China experiences severe particulate matter (PM) pollution in many of its cities. Meteorological factors are critical in determining both areal and temporal variations in PM pollution levels; understanding these factors and their interactions is critical for accurate forecasting, comprehensive analysis, and effective reduction of this pollution. This study analyzed areal and temporal variations in concentrations of PM2.5, PM10, and PMcoarse (PM10 - PM2.5 ) and PM2.5 to PM10 ratios (PM2.5 /PM10 ) and their relationships with meteorological conditions in 366 Chinese cities from January 1, 2015 to December 31, 2017. On the national scale, PM2.5 and PM10 decreased from 48 to 42 μg m − ³ and from 88 to 84 μg m − ³, respectively, and the annual mean concentrations were 45 μg m − ³ (PM2.5 ) and 84 μg m − ³ (PM10 ) during the time period (2015–2017). In most regions, largest PM concentrations occurred in winter. However, in northern China, in spring PMcoarse concentrations were highest due to dust. The PM2.5 /PM10 ratio was higher in southern than in northern China. There were large regional disparities in PM diurnal variations. Generally, PM concentrations were negatively correlated with precipitation, relative humidity, air temperature, and wind speed, but were positively correlated with surface pressure. The sunshine duration showed negative and positive impacts on PM in northern and southern cities, respectively. Meteorological factors impacted particulates of different size differently in different regions and over different periods of time. Graphical abstract: Image 1 Highlights: Areal-temporal patterns of different-sized PM in 366 Chinese cities were analyzed. Areal-temporal variations of PM2.5 /PM10 were explored in China at multiple scales. Annual mean concentrations of different-sized PM decreased from 2015 to 2017. Correlations between different-sized PM and meteorology in China were investigated. Abstract : Pollution of PM2.5, PM10, and PMcoarse and PM2.5 /PM10 ratios and their correlations with meteorological conditions showed great areal-temporal disparities in China.